2021
DOI: 10.3168/jds.2020-19101
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic transcriptomic adaptation from prepartum to postpartum in dairy cows

Abstract: The transition from pregnancy to lactation is the most challenging period for high-producing dairy cows. The liver plays a key role in biological adaptation during the peripartum. Prior works have demonstrated that hepatic glucose synthesis, cholesterol metabolism, lipogenesis, and inflammatory response are increased or activated during the peripartum in dairy cows; however, those works were limited by a low number of animals used or by the use of microarray technology, or both. To overcome such limitations, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 80 publications
1
8
0
Order By: Relevance
“…Though the library prep kit used is apt at maximizing sequencing depth when compared with other commercial solutions, we noticed that many transcripts with (typically) a relatively low expression were either not detected or detected at very low level, with zero-counts in most samples. Despite being able to detect >14,000 transcripts with a count>4 in at the least one sample, which is somewhat similar to what previously reported in RNAseq analysis of bovine liver (125)(126)(127), many transcripts with a relatively medium-low expression were either not detected or detected at very low level, with lack of detection in most samples. Most of the genes used for the RT-qPCR were in this category, such as all PPAR transcripts and LIPC.…”
Section: Novel Ppar Targets Are Likely Involved In Regulation Of Infl...supporting
confidence: 87%
“…Though the library prep kit used is apt at maximizing sequencing depth when compared with other commercial solutions, we noticed that many transcripts with (typically) a relatively low expression were either not detected or detected at very low level, with zero-counts in most samples. Despite being able to detect >14,000 transcripts with a count>4 in at the least one sample, which is somewhat similar to what previously reported in RNAseq analysis of bovine liver (125)(126)(127), many transcripts with a relatively medium-low expression were either not detected or detected at very low level, with lack of detection in most samples. Most of the genes used for the RT-qPCR were in this category, such as all PPAR transcripts and LIPC.…”
Section: Novel Ppar Targets Are Likely Involved In Regulation Of Infl...supporting
confidence: 87%
“…One of the significant roles it plays in dairy cows from the point of view of economic interest is controlling the synthesis of milk fat in dairy cows, not only in mitochondria but also with ELVOL participating in the regulation of peroxisomal β-oxidation. PPARγ expression increases during changes in the lactation period [55,56], thereby regulating peroxisomal β-oxidation to prevent metabolic stress. Research further confirmed the importance of PPARγ in regulating milk fat production [57,58].…”
Section: Pparγmentioning
confidence: 99%
“…We speculate the functioning of the transcription factor not only depends on its quantity but is also determined by its activity and intracellular location. Similarly, even though it is well recognized that PPAR has an important role in the adaptation of the liver to the transition period in dairy cows, the gene or protein expression of its isotypes such as PPARA (the gene symbol of PGC-1 α ) and PPARG had no significant changes during the transition period ( Bionaz et al., 2015 ; Gao et al., 2021 ; Schaff et al., 2012 ). Therefore, although the transcription level of PGC-1 α has not been improved, its activation and location may be regulated by post-translational modification, which may involve the regulation of protein kinase mTORC1 ( Cunningham et al., 2007 ).…”
Section: Discussionmentioning
confidence: 99%